1978
DOI: 10.1093/nar/5.7.2493
|View full text |Cite
|
Sign up to set email alerts
|

Denaturation maps of DNA: experimental and theoretical maps of ø×174 DNA

Abstract: A formaldehyde denaturation map of the replicative form of phiX174 DNA is obtained. The RFI DNA was converted into a linear state by restriction endonuclease pst I which introduces into this DNA a single double-stranded break. The map has four clear-cut peaks. Their positions excellently correlate with the peak positions on the map of equilibrium denaturation theoretically obtained earlier from the known nucleotide sequence of phiX174 DNA. The sequence is also used for a calculation of the maps of smoothed AT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…No apparent correlation with the percentage of A-T in these 'immediate regions exists since it approximates the overall percentage of A-T for the molecule in each case. However maps of "smoothed out" A-T content over significantly longer regions (100-200 bp) show localized peaks of A-T content which coincide precisely with the denatured regions (70). Some other correlations of interest can be drawn.…”
Section: Discussionmentioning
confidence: 95%
“…No apparent correlation with the percentage of A-T in these 'immediate regions exists since it approximates the overall percentage of A-T for the molecule in each case. However maps of "smoothed out" A-T content over significantly longer regions (100-200 bp) show localized peaks of A-T content which coincide precisely with the denatured regions (70). Some other correlations of interest can be drawn.…”
Section: Discussionmentioning
confidence: 95%
“…The results of such calculations may be compared with experimental data on optical melting and electron microscopic mapping. Such a study completed recently for 0x174 DNA has yielded very promisinig results (3,4). In the present paper we report the results of computations of melting profiles and denaturation maps for fdDNA and its restriction fragments.…”
mentioning
confidence: 78%
“…lb and 2b), which correspond to A* T-rich regions (adenine, thymine). The distinct peaks representing less stable DNA regions are not necessarily indicative of a very high local concentration of A and T bases, since it has been shown that only a few percent increase in the A + T content if extended over a few hundreds of base pairs gives rise to a distinct sharp peak in a denaturation map (18). The maps of the polymerase binding regions were carefully aligned with the denaturation maps in Figs.…”
mentioning
confidence: 99%